Legal Analysis Of Human Trafficking Case As A Transnational Organized Crime That Is Threatening State Security - Prasetya, Yuda (Lex Scientia Law Review, 2020)
Human trafficking is a form of transnational crime. One of the cases that occurred in 2019 was the torture of one of the Female Workers even being made a sexual gratification is one proof of the cruelty of human trafficking. Several Conventions have been held to prevent human trafficking. The UN in 2000 issued the Palermo Protocol on Preventing, Eradicating and Punishing Trafficking in Persons. The perpetrators of human trafficking have violated human rights because of exploitation. The Government of Indonesia issued The Act Number 21 of 2007 concerning the Eradication of the Criminal Act of Trafficking in Persons as an action to prevent trafficking in persons. Efforts to protect victims are also carried out by protecting, helping to resolve victims' problems and repatriating victims.